THE EFFECTIVENESS OF USING AUDIO VISUAL LEARNING MEDIA ON SPORTS PHYSIOLOGY LEARNING FOR PHYSICAL EDUCATION STUDENTS - Purbangkara, Tedi; Hukubun, Mariana Ditboya; Tomasoa, Yellia; Siswanto; Ryanto, Aria Kusuma Yuda (JUARA : Jurnal Olahraga, 2025)
This study aims to determine the effectiveness of audio-visual learning media in improving students' understanding of sports physiology in Physical Education programs. The research employed a pre-experimental design with a one-group pretest-posttest approach, involving 35 students who were taught using audio-visual learning media. Data were collected through pretest and posttest assessments, as well as student response questionnaires. The results showed a significant increase in students’ scores, with the average score rising from 60.86 in the pretest to 76.29 in the posttest, indicating an improvement of 15.43 points or approximately 25.4%. Additionally, questionnaire results revealed that most students responded positively to the use of audio-visual media, stating that it made the learning process more engaging, interactive, and easier to understand. This suggests that audio-visual learning media is effective in enhancing learning outcomes and student motivation in sports physiology courses. Although this study has limitations due to the absence of a control group, it provides valuable insights into the potential benefits of integrating technology-based media in physical education curricula.